Navarre, Dickinson County - Coup, Adam (Kansas State University, The Chapman Center for Rural Studies, 2012)
Navarre was organized around the school, the church, and starting in 1887, the Atchison, Topeka, and Santa Fe railroad. Fire destroyed much of the town in 1939, and it never recovered.
Adam Coup, “Navarre, Dickinson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/140.
Keywords: Dickinson County; fire; Kansas; Lost Towns; Navarre; Railroad